Low-dimensional nanomaterials for electrochemical biosensing of gastric cancer biomarkers in whole blood: Current trends and future Prospects - Zengkai Ji; Yao Li; Shuijian He; Jian Ju; Yongfeng Chen (Materials Today Bio)
Gastric cancer is one of the malignant tumors with a high global incidence and is one of the major public health challenges worldwide. The early diagnosis of gastric cancer has the potential to significantly enhance patient survival rates. Electrochemical biosensors possess the capability to detect biomarkers at low concentrations in whole blood samples, which has sparked considerable interest in their potential clinical applications. This review provides an overview of the role of structural diversity of low dimensional nanomaterials on the sensitivity and specificity approach of electrochemical biosensors. Furthermore, we highlight recent advancements in the development of electrochemical sensors for the detection of various gastric cancer biomarkers in blood samples. This review elucidates the design principles and performance metrics of these sensors, including their sensitivity and specificity. Finally, we address the issues currently encountered by electrochemical biosensors in the detection of gastric cancer and discusses the barriers to their clinical application, and propose potential solutions to these challenges.